Modeling Total Maintenance Cost of a Repairable System in Some Bounded Time Interval - S Suyono; J.A.M. van der Weide (Jurnal ILMU DASAR, 2011)
In this paper we model the total maintenance cost of a repairable system where the inter-maintenance times are modeled as discrete-time and continuous-time renewal processes. The maintenance cost is assumed to be a function of the lifetime of the system. We derive the probability distribution, including the mean and the variance, of the total maintenance cost. The results are presented in the form of generating functions and Laplace transforms that in general have to be inverted numerically. Some examples are presented in this paper.